2013
DOI: 10.3354/dao02662
|View full text |Cite
|
Sign up to set email alerts
|

Batrachochytrium dendrobatidis in Germany: distribution, prevalences, and prediction of high risk areas

Abstract: In Germany, the pathogenic fungus Batrachochytrium dendrobatidis (Bd) was detected in 11 indigenous frog species, 4 newt species, and 1 salamander species in 64 out of the 181 locations (35%) investigated. Among the 3450 samples collected between 2003 and 2011, 284 (8.2%) were positive for Bd infections. The highest prevalences were observed in Alytes obstetricans (17.8% of individuals, 20% of populations), followed by Ichthyosaura alpestris (14.7%, 22.2%), Bombina variegata (13.9%, 38.5%), and water frogs c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 53 publications
1
9
0
Order By: Relevance
“…While prevalence varies between 4.5% and 32%, infection intensities are generally low [11,14,16,[20][21][22][23][24]. Nonetheless, lethal chytridiomycosis has been observed in the Apennine (continental Italy) subspecies of yellow-bellied toad, B. variegata pachypus [25].…”
Section: Materials and Methods (A) Study Species And Areamentioning
confidence: 99%
“…While prevalence varies between 4.5% and 32%, infection intensities are generally low [11,14,16,[20][21][22][23][24]. Nonetheless, lethal chytridiomycosis has been observed in the Apennine (continental Italy) subspecies of yellow-bellied toad, B. variegata pachypus [25].…”
Section: Materials and Methods (A) Study Species And Areamentioning
confidence: 99%
“…To date, in the literature only Sura et al (2012), referring to personal communication with T. Ohst, have reported that a German−Swiss research team detected Bd in 29 of 161 sampled water frogs from 5 localities, but georeferenced data are unavailable. Therefore, Bd in Poland should be treated as insufficiently investigated, although the fungus has commonly been observed in neighboring countries (Ohst et al 2013, Baláž et al 2014a. The aim of our study was a survey of the Bd presence in Poland, as it is a potential factor in fluctuations or decreases in local amphibian populations.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is listed as highly endangered for Germany and also for the federal state of Hesse (Kühnel et al 2009, Alfermann et al 2010. Although chytridiomycosis has not been suggested to play a main role in yellow-bellied toad declines (Kuzmin et al 2009) and outbreaks of chytridiomycosis have not yet been observed in any amphibian species in Germany, impacts on populations cannot be ruled out (Ohst et al 2013) without long-term monitoring of infected populations.…”
Section: Introductionmentioning
confidence: 99%
“…In a European-wide study on Bd infections, members of the families Alytidae and Bombinatoridae were significantly more likely to be infected than other European amphibian groups, and the highest infection rates were found in juvenile yellow-bellied toads Bombina variegata from Hungary (Baláž et al 2014). Hence, B. variegata is at least a tolerant species, and the question is if the species or populations/individuals are also susceptible to chytridiomycosis (see Van Rooij et al 2015) In Germany, Bd-infected individuals have been found in populations of almost all autochthonous amphibian species (Lötters et al 2012, Ohst et al 2013. In the first nationwide Bd screening by Ohst et al (2013), 15 out of 108 tested yellow-bellied toads and 5 out of 13 tested populations were infected with Bd.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation